E-procurement adoption in the Malaysian construction sector : integrating diffusionof innovations and theory of planned behaviour framework - Noorsaidi Mahat,; Asmah Alia Mohamad Bohari,; Mohd Azrai Azman,; Natasha Khalil,; Amira Shazlin Adnan,; Mohd Iskandar Abd Malek, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In recent years, environmental problems have become more prominent in the construction industry. The production and use of building materials are still one of the main reasons for various ecological and environmental challenges in the industry. Compared with traditional building materials, green building materials are environmentally friendly. Therefore, the adoption of green building materials in the construction industry can generally solve the industry’s ecological and environmental problems and promote green and low-carbon development. Research on contractors’ green procurement behaviour can promote the construction industry’s sustainable development. Many scholars discuss and agree that the implementation of e-procurement is a green approach towards sustainable construction. However, current evidence indicates that procurement stakeholders, especially contractors, are struggling to implement e-procurement effectively. Therefore, there is a need to study contractors’ behaviour in relation to green e-procurement. In response, this study investigates the adoption of e-procurement by Malaysian contractors by adopting planned behaviour theories and diffusion of innovations in their decision-making process. Here, a conceptual framework has been developed which focuses on factors influencing contractors’ adoptions. The framework can be used for understanding the contractors’ adoption decision of e-procurement. The result will help to find the critical key factors affecting green procurement behaviour from contractors’ perspectives and extend the theories further. This framework is also in tandem with the Construction Industry Development Board (CIDB), Construction 4.0 Strategic Plan (2021-2025) in identifying critical factors that affect the adoption of green procurement on construction projects.